Is philosophy androcentric? - Landau, Iddo, 1958- (Pennsylvania State University Press, 2006)
In Is Philosophy Androcentric?, Iddo Landau contends that none of the arguments for viewing philosophy as pervasively androcentric ultimately stand up to rational scrutiny, while the ones that show it to be nonpervasively androcentric do not undermine it in the way that many critics have supposed. "Philosophy emerges, in almost all of its parts," he concludes, "as human rather than male, and most parts and aspects of it need not be rejected or rewritten."